THE IMPORTANCE OF CROSS –CONTAMINATION CONTROL WITH LAB MADE RESTORTIONS - Abdelssadk Hamed, Khadiga (Scientific Journal of University of Benghazi, 2026)
The infection control measurements and guidelines should be strongly encouraged. to ensure aseptic practice in dental clinics and laboratories to avoid cross contamination .The ecologic relationships between micro- organisms and humans are exemplified in the oral flora . The microflora of the oral cavity consist of bacteria, yeasts, certain fungi, , and mycoplasmas,.. It’s estimated that 500-600 different kinds of bacteria thrive on mucus and food remnants in the mouth. A predominant member of this community is the Gram positive bacterium Streptococcus mutans. The principal potential route of transmission from the patient to the dental technician is through contaminated impressions, casts and prostheses. It has been demonstrated that microorganisms can be recovered from casts. It would seem essential therefore, that impressions should be disinfected by the clinician or a suitably protected technician prior to the initiation of any laboratory procedures.